B Oxidized PKARIα protects against ischemia-reperfusion injury by inhibiting lysosomal-triggered calcium release. (17th July 2020) - Simon, Jillian N; Vrellaku, Besarte; Monterisi, Stefania; Chu, Sandy; Rawlings, Nadiia; Lomas, Oliver; Marchal, Gerard A; Waithe, Dominic; Gajendragadkar, Parag; Jayaram, Raja; Sayeed, Rana; Channon, Keith M; et al.
Abstract : Reperfusion-induced calcium overload profoundly affects the extent of myocardial injury following ischemia, impacting long-term morbidity and mortality. Reactive oxygen species play a crucial role in shaping the amplitude and spatiotemporal patterns of the intracellular calcium signal, but the mechanism governing this interplay remain unclear. Here we show that, in vivo, myocardial ischemia and reperfusion (I/R) potently induce formation of an intermolecular-disulfide within the type I regulatory subunits of protein kinase A (PKARIα), both in mice and in humans. This conformation does not increase intrinsic PKA catalytic activity, but rather promotes AKAP-mediated subcellular compartmentalization of PKARIα to the lysosome, where it inhibits calcium release from two-pore channels and prevents global calcium release from nearby ryanodine receptors. This regulatory mechanism is shown to be crucial for limiting I/R-induced cell death, as 'redox dead' Cys17Ser PKARIα knock-in mice, which are incapable of undergoing RIα disulfide formation, display substantially larger infarct sizes with concomitant reductions in left ventricular contractile recovery, both of which are prevented by inhibition of lysosomal calcium release at the time of reperfusion. These findings reveal a hitherto unknown role for PKARIα, in its disulfide-activated state, to regulate calcium homeostasis and, in this way, potently protect the myocardium from post-ischemic injury.